Economic Impact of Public Markets: Effects of Resident and Tourist Consumption in Brazil and Internationally - Silva, Milo Andrade da; Soares, Jakson Renner Rodrigues; Solla, Xosé Manuel Santos (Revista JRG de Estudos Acadêmicos, 2025)
Introduction: Public markets are essential to the local economy, functioning as commercial centers that attract both residents and tourists. In addition to their commercial functions, these markets are important for the cultural promotion and economic development of the regions in which they are located. In the tourism scenario, public markets stand out as attractions that boost economic flow, generating income through the consumption of visitors. This study aims to explore the impact of this consumption on public markets, both in Brazil and internationally, and how these dynamics manifest themselves in different cultural and economic contexts. Objective: The objective of this research is to evaluate the economic impact of public markets, focusing on the effects of consumption by residents and tourists in different regions of Brazil and the world. The study seeks to identify how these markets contribute to local economic development and the variables that influence this impact, considering regional and international differences. Method: The research adopted a scoping review methodology, which included the analysis of academic literature, economic reports and case studies published in the last fifteen years. The scoping review allowed mapping the evidence on the economic impact of public markets, considering the consumption dynamics of tourists and residents. Studies that addressed the relationship between public markets and economic development, the role of markets in the tourism sector, and the strategies used to maximize local economic benefits were included. Results: The results of the review indicate that public markets have a significant economic impact on local economies, especially in areas with high tourist activity. In Brazil, as in other parts of the world, these markets attract both residents and tourists, generating considerable revenues that benefit local traders and producers. Internationally, it has been observed that tourist consumption in public markets can serve as an engine for local economic growth, particularly in sectors such as food, crafts, and cultural tourism. However, the success of these markets depends on effective management, adequate infrastructure, and marketing strategies aimed at attracting both residents and tourists. Final Considerations: This study demonstrates that public markets are fundamental to the economic development of the regions in which they operate, acting as consumption hubs for residents and tourists. Comparative analysis between Brazil and other international contexts suggests that, although there are variations in practices and impacts, public markets have the potential to foster sustainable economic growth, as long as they are supported by appropriate public policies and management strategies that value both local culture and the visitor experience.